Characteristics of antimicrobial peptide OaBac5mini and its bactericidal mechanism against Escherichia coli - Shen, Shanshan; Sun, Yawei; Ren, Fei; Blair, Jessica M. A.; Siasat, Pauline; Fan, Shuaiqi; Hu, Jianhe; He, Junping (Frontiers in Veterinary Science, 2023)
Antimicrobial peptides (AMPs) play an important role in defending against the attack of pathogenic microorganisms. Among them, the proline-rich antibacterial peptides (PrAMPs) have been attracting close attention due to their simple structure, strong antibacterial activity, and low cell toxicity. OaBac5mini is an active fragment of the sheep-derived OaBac5 belonging to the PrAMPs family. In this study, we demonstrated the characteristics of OaBac5mini and its bactericidal mechanism against Escherichia coli. The susceptibility test demonstrated that OaBac5mini showed potent antibacterial activity against the multidrug-resistant (MDR) E. coli isolates (MIC 1.95-3.26 μg/mL). It is noticeable that the absence of inner membrane protein SbmA in E. coli ATCC 25922 caused the MIC of OaBac5mini to increase 4-fold, implying OaBac5mini can enter into the cytoplasm via SbmA and plays its antibacterial activity. Moreover, the antibacterial activity of OaBac5mini against E. coli ATCC 25922 was not remarkably affected by the serum salts except for CaCl2 at a physiological concentration, pH, temperature, repeated freeze-thawing and proteases (trypsin < 20 μg/mL, pepsin or proteinase K). Time-kill curve analysis showed OaBac5mini at the concentration of 200 μg/mL (8×MICs) could effectively kill E. coli ATCC 25922 after co-incubation for 12 h. In addition, OaBac5mini (25 to 400 μg/mL) was not hemolytic against rabbit red blood cells and also was not cytotoxic to porcine small intestinal epithelial cells (IPEC-J2). Bioinformatic analysis indicated that OaBac5mini is a linear peptide with 8 net positive charges. Furthermore, OaBac5mini (25, 50, 100, and 200 μg/mL) significantly increased the outer membrane permeability and impaired the inner membrane integrity of E. coli ATCC25922. At the same time, some atrophy, corrugation and pores were also found on the cell surface. In conclusion, OaBac5mini is a stable and potent PrAMP that kills E. coli by two different modes of action: inhibiting intracellular target (s) and damaging cell membrane.